The correlation between clinical type of acne and quality of life in acne vulgaris patients - Akça, Hanife Merve; Tuncer Kara, Kevser (OrtadogÂŸu Reklam Tanitim Yayincilik Turizm Egitim Insaat Sanayi ve Ticaret A.S., 2020)
Objective: Acne vulgaris is a chronic inflammatory disease that affects the pilosebaceous unit. Acne, is a common skin disease, that affects 80% of the population at some point in their lives. While 60% of the cases may be controlled with short-term and mild treatments, 40% may persist until the adulthood. Although acne formation affects the physical appearance of the person and leaves a scar, it may also be the cause of psychological problems such as depression, anxiety, and social inhibition. The aim of this study is to examine the relationship between the clinical severity of acne and quality of life. Material and Methods: A total of 100 patients diagnosed with acne vulgaris were included in the study. The patients' age, gender, duration of the disease, and local and systemic treatments that were received before and acne severity scores were recorded. Acne quality of life questionnaire (Acne-QoL) was applied and total scores were determined. Results: The average of the Acne-QoL scores was 16±5.22, and there was no statistically significant difference between the mild-moderate and severe acne groups in terms of quality of life (p>0.05). Conclusion: Although acne affects the physical appearance, it may also greatly affect the quality of life of patients in mild and moderate clinical types. © 2020 OrtadogÃ‚ÂŸu Reklam Tanitim Yayincilik Turizm Egitim Insaat Sanayi ve Ticaret A.S.. All rights reserved.
Akne Vulgaris Hastalarında Aknenin Klinik Tipinin Yaşam Kalitesi ile İlişkisi
Keywords: Acne; Quality of life; Severe acne